UNBK: TRANSFORMASI SISTEM EVALUASI STANDAR NASIONAL DI ERA REVOLUSI INDUSTRI 4.0 - Syarif Hidayatullah; Ismail Marzuki; Lukmanul Hakim (Universitas Muhammadiyah Tangerang, 2020)
Education is the process of transferring knowledge. In the process, it is necessary to design a quality curriculum. In the curriculum, one of the essential things is evaluation. Educators can make evaluations to students in order to obtain information on student development. In the national education system, the state pays great attention to education. The state's attention in education is to hold a national exam to equalize the quality of education in Indonesia. The national standard evaluation system is still changing in terms of terms and technicalities. Recently, computer-based evaluation systems are the latest step and innovation. Especially in the current era of the industrial revolution 4.0, digitization systems are in all aspects of life, including in the world of education. Since 2014, the national standard education evaluation system began using the online examination system. Although in 2014, not all of the schools in Indonesia were able to conduct and access computer-based examinations with the internet network. The program requires sufficient time for socialization and technical preparation. The spirit of revolution 4.0 is marked by building a digitalized national standard evaluation system. Even in response to the development of the Industrial Revolution era 4.0, Indonesia has made innovative breakthroughs in the world of education, namely the Computer Based National Examination (UNBK) system